Comparison of Divorce between Muslims in Australia and Muslims in Indonesia Based on the Laws of Each Country - Andhika Septian Anharil Huda (al-Afkar, Journal For Islamic Studies, 2024)
Divorce is something that often happens to a family, including Muslim families living in Australia and Indonesia. In resolving problems caused after divorce, you must follow the regulations that apply to each country. In Australia regulations regarding divorce are included in the Family Law, namely in Australia's Marriage Act 1961 (Cth). Meanwhile in Indonesia it is listed in Law Number 1 of 1974 and the Compilation of Islamic Law (KHI). This article will discuss several differences between the Family Laws in Australia and Indonesia. The laws in these two countries definitely have similarities. However, behind the similarities, of course there are also differences. This research is normative or literature research. The approach used is a qualitative approach. Then the data in this research is secondary data sourced from legal material from Australia and Indonesia. By using a comparative study method between the two components studied. So at the end several differences regarding family law issues will be shown in the laws of the two countries. From the results of the discussion, it can be concluded that in Australia Muslims are given the authority to divorce according to their choice, which can be done according to Islamic law or through regulatory procedures in Australia. Meanwhile, Muslim divorces in Indonesia are only considered valid if they are carried out in court.